Respon Pertumbuhan Semai Tanjung (Mimusops elengi Linn) Terhadap Pemberian Pupuk Kandang Ayam: Response of Seedling Growth of Tanjung (Mimusops elengi Linn.) to Doses of Chicken Manure Fertilizer - Puri, Suci Ratna; Hamzah, Hamzah; Handayani, Rajjitha; Rif'atunidaudina, Ria; Rumondang, Jenny; Armada, Galang (Jurnal Silva Tropika, 2024)
ABSTRACT The sufficiency of nutrients in the soil greatly affected the growth and development of plants. The type of plant largely determines its nutritional requirement. Tanjung (Mimusops elengi Linn.) is one of type the forestry plant that has the ability of adapt to air pollution, so that it making it potential to be developed as a protective tree in urban forest development programs. The objective of this research was to determine how the Tanjung seedling growth responds to the dose of chicken manure in the nursery of the Agriculture Faculty, Jambi University. The study used a completely randomized design with a dose of chicken manure as the treatment. The treatments consisted of 5 levels, namely without chicken manure, 500 g/polybag, 750 g/polybag, 1000 g/polybag, and 1250 g/polybag. The research results showed that the dose of chicken manure affected on growth of Tanjung seedlings. The application of 1250 g of chicken manure per polybag had best effect on diameter, number of leaves, shoot dry weight, total dry weight, and root shoot ratio.   Keywords: chicken manure, doses, growth, seedling of Mimusops elengi, ultisol soil   ABSTRAK Kecukupan unsur hara dalam tanah sangat mempengaruhi pertumbuhan dan perkembangan suatu tanaman. Kebutuhan akan nutrisi sangat ditentukan oleh jenis tanaman itu sendiri. Tanjung (Mimusops elengi Linn.) merupakan salah satu tanaman kehutanan yang yang memiliki kemampuan adaptasi terhadap polusi udara sehingga berpotensi untuk dikembangkan sebagai pohon pelindung pada program pengembangan hutan kota. Tujuan penelitian ini adalah untuk menentukan dosis pupuk kandang yang optimal untuk pertumbuhan bibit tanjung. Penelitian ini menggunakan rancangan acak lengkap dengan dosis pupuk kandang ayam sebagai perlakuan yang terdiri atas 5 taraf yaitu tanpa pemberian, 500 g/polibag, 750 g/polybag, 1000 g/polybag, and 1250 g/polybag. Hasil penelitian menunjukkan dosis pemberian pupuk kandang ayam berpengaruh terhadap pertumbuhan bibit tanjung. Perlakuan pupuk kandang dengan dosis 1250 g/polybag memberikan respon pertumbuhan terbaik terhadap diameter, jumlah daun, berat berat kering tajuk, berat kering total dan nisbah tajuk akar pada bibit tanjung.   Kata kunci: dosis, pertumbuhan, pupuk kandang ayam, semai tanjung, tanah ultisol